Mechanistic study of C–H bond activation by O2 on negatively charged Au clusters: α, β-dehydrogenation of 1-methyl-4-piperidone by supported Au catalysts. Issue 10 (26th March 2021) - Miyazaki, Ray; Jin, Xiongjie; Yoshii, Daichi; Yatabe, Takafumi; Yabe, Tomohiro; Mizuno, Noritaka; Yamaguchi, Kazuya; Hasegawa, Jun-ya
Abstract : Aerobic C–H activation by Au/OMS-2 catalyst is driven by charge transfer from OMS-2 to adsorbed O2 via Au cluster. Abstract : Au nanoparticles supported on the manganese oxide octahedral molecular sieve OMS-2 can efficiently catalyze α, β-dehydrogenation of β- N -substituted saturated ketones using O2 as the terminal oxidant. However, despite the utility of this reaction, the active sites and the reaction mechanism remain unclear. Here, the reaction mechanism for the Au/OMS-2-catalyzed aerobic α, β-dehydrogenation of 1-methyl-4-piperidone was investigated mainly by using density functional theory (DFT) calculations. From control experiments under various reaction conditions, we found that O2 plays an important role in the α, β-dehydrogenation over Au nanoparticles. Thus, we attempted to clarify the mechanism for the α, β-dehydrogenation of 1-methyl-4-piperidone on Au nanoparticle catalysts by DFT calculations using Au cluster models. The reaction was found to cleave the C–H α and C–H β bonds in that order. An O2 molecule adsorbed on the negatively charged Au cluster caused by charge transfer from OMS-2 was found to be sufficiently activated to abstract the H α atom in the 1-methyl-4-piperidone substrate. This indirect H α abstraction by the activated O2 was energetically more favorable than direct H α abstraction by the Au cluster. The subsequent H β abstraction was found to be promoted by adsorbed oxygen species ( i.e., HOO, OH, and O) formed after the H α abstraction. The reaction mechanism proposed in this study provides general insight into the aerobic C–H bond activation by supported Au catalysts.